The effect of Multimedia Method of Education on Weight loss in Hemodialysis Patients - M Davoudi; Y Mohammadi; E Yazdanparast; H Ahmadi Chenari; H Eslami; R Rajabi; AA Jesmi (Iran University of Medical Sciences, 2016)
Abstract Background & Aim: Overweight and its consequences are the most important complications in hemodialysis patients. Weight Control is an important educational need in hemodialysis patient. Multimedia technology provides easy and stable learning by various forms of interaction. The present study carried out to determine the effect of multimedia training method to weight management in hemodialysis patients. Material & Methods: In a quasi-experimental research 30 hemodialysis patients were divided based on random allocation in two intervention and control groups. Data were collected by demographic data form and standardized weighing scale. In the intervention group training were given about methods of weight control. Weight measurement of patients performed before and after training. Data were analyzed using SPSS software ver. 18.0 while descriptive statistics and independent t-test were applied. Results: Comparison of means demonstrated that change in the body weight in intervention group is more than control group (1.63±1.55 VS 0.43±1.07).The average weight change between intervention and control group was significant (P<0.05). Conclusion: Multimedia training method was effective on weight loss in hemodialysis patients as a result this method may improve the weight management of hemodialysis patients.